Influence Social Media Marketing Activity on Repurchase Intention in The E-Commerce Industry - Hangestyo Leksono; Sekar Prasetyaningtyas (Journal of Research in Business, Economics, and Education, 2021)
The study’s goal is to assess the influence of social media activity marketing on e-commerce in Indonesia and to give suggestions to e-commerce company management. Knowing the impact of social media marketing activity on brand equity in e-commerce in Indonesia, knowing the effect of social media marketing activity on customer relationships in e-commerce in Indonesia, knowing the effect of social media marketing activity on repurchase intention on e-commerce in Indonesia, knowing the effect of brand equity on repurchase intention on e-commerce in Indonesia, and knowing the effect of customer relationships on repurchase intention on e-commerce in Indonesia. This research uses a quantitative approach and SmartPLS with SEM method for data analysis. This study uses research methods survey methods of data collection with online questionnaires, the population and sampling technique for social media users in Indonesia with the criteria of men and women who have used social media and made purchases on E-commerce within the last 3 months and uses 210 sample. The results of this study explain that customer relationship has no significant influence on repurchase intention directly but shows a strong and significant positive relationship between social media marketing activities and brand equity as a mediation on repurchase intention so that brand equity is the main and biggest factor influencing repurchase intention. In this study, companies can take advantage of increasing several important factors in the company, especially repurchase intention, which is the main discussion in this study in the e-commerce industry so that companies can take an overview of the condition of e-commerce in Indonesia.